The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3892/ol.2017.7207
|View full text |Cite
|
Sign up to set email alerts
|

Leucine‑rich repeat‑containing G protein‑coupled receptor 5 and CD133 expression is associated with tumor progression and resistance to preoperative chemoradiotherapy in low rectal cancer

Abstract: Preoperative chemoradiotherapy has been performed as a standard therapy for advanced low rectal cancer. Cancer stem cells (CSCs) have been reported to contribute to resistance to treatment and patient prognosis. Leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5) and cluster of differentiation (CD133) are putative markers for CSCs. However, their prognostic ability remains unknown, and evaluation of a single marker can be insufficient due to the heterogeneity of cancer. LGR5 and CD133 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…CD133 positivity was defined as >5% positively stained cancer cells, consistent with results from our previous study of CD133 expression in colorectal polyps and cancer (11,17). Moreover, LGR5 positivity was defined as >50% positively stained cancer cells, in accordance with our previous study of LGR5 expression in rectal cancer tissue after chemoradiotherapy (18). The sections were independently analyzed in vivo 33: 1279-1284 (2019) 1280 In some glands, intraglandular cellular debris was also CD133-positive ( Figure 1).…”
Section: Cd133 and Lgr5 Immunohistochemical Stainingsupporting
confidence: 87%
“…CD133 positivity was defined as >5% positively stained cancer cells, consistent with results from our previous study of CD133 expression in colorectal polyps and cancer (11,17). Moreover, LGR5 positivity was defined as >50% positively stained cancer cells, in accordance with our previous study of LGR5 expression in rectal cancer tissue after chemoradiotherapy (18). The sections were independently analyzed in vivo 33: 1279-1284 (2019) 1280 In some glands, intraglandular cellular debris was also CD133-positive ( Figure 1).…”
Section: Cd133 and Lgr5 Immunohistochemical Stainingsupporting
confidence: 87%
“…Immunohistochemistry. All the samples for immunohistochemical analysis were obtained from paraffin-embedded (FFPE) specimens and stained as previously reported (23). The primary antibodies used were as follows: β-catenin (dilution 1:500; BD Transduction Laboratory, San Diego, CA, USA), TP53 (dilution 1:100; Dako, Glostrup, Denmark), MLH1 (dilution 1:50; Dako), PMS2 (dilution 1:50; Dako), MSH2 (dilution 1:50; EMD Millipore, Darmstadt, Germany), and MSH6 (dilution 1:50; BD Transduction Laboratory).…”
Section: Methodsmentioning
confidence: 99%
“…Various biomarkers are associated with response to CRT in rectal cancer, including the expression of p53, Ki67, thymidylate synthase, and CD133, as well as alterations in KRAS . Furthermore, several studies have reported gene expression signatures using microarray that predict responses to CRT in rectal cancer .…”
Section: Introductionmentioning
confidence: 99%